Swiss Climate Change and Nuclear Policy: A Comparative Analysis Using an Energy System Approach and a Sectoral Electricity Model - Nicolas Weidmann; Ramachandran Kannan; Hal Turton (Swiss Journal of Economics and Statistics, 2012)
Decisions on climate change and nuclear policies are likely to have major influences on the future evolution of the Swiss energy system. To understand the implications of selected future policy decisions, we analyse the development of the Swiss energy system with a bottom-up technology-rich least-cost optimisation modelling framework. We use the Swiss MARKAL energy system model and analyse a stringent climate change mitigation policy with two policy variants on the availability of nuclear energy, i.e. with and without nuclear new builds. The energy system modelling approach provides insights into system-wide energy pathways, technology choice and cross-sectoral trade-offs like resource competition, electrification, and CO2 mitigation options across supply and demand sectors. To complement the full system approach, we apply an experimental TIMES model – a successor to MARKAL – of the Swiss electricity sector with a detailed representation of the electricity load curve accounting for diurnal and seasonal variations in demand and resource supply. The analytical results from both modelling approaches are presented and the electricity sector results compared to illustrate the complementary policy insights. The implications for realising an ambitious climate target with and without investment in new nuclear plants are discussed, and a number of areas for possible policy support identified.
Keywords: Q40; Q41; Q42; Q49; Q54; Q56; 330; MARKAL energy system model; TIMES electricity model; Swiss climate policy; Scenario analysis